Mitochondrial stress response gene Clpp deficiency impairs oocyte competence and deteriorate cyclophosphamide-induced ovarian damage in young mice - Li, Guangxin; Gu, Jingkai; Zhou, Xiaomei; Wu, Ting; Li, Xian; Hua, Renwu; Hai, Zhuo; Xiao, Yuan; Su, Jiaping; Yeung, Willian S. B.; Liu, Kui; Guo, Chenxi; et al. (Frontiers in Endocrinology, 2023)
Chemotherapy is extensively used to treat cancers and is often associated with ovarian damage and leads to premature ovarian insufficiency and infertility, while the role of mitochondria during ovarian damage with chemotherapy remains unknown. This study used a mouse model with oocyte-specific deletion of mitochondrial stress response gene Caseinolytic peptidase P (Clpp) to investigate mitochondrial homeostasis in oocytes from mice receiving a chemotherapeutic drug cyclophosphamide (CTX). We found that oocyte-specific deletion of Clpp reduced fecundity of the mice at advanced age. The deletion led to meiotic defects with elevated abnormal spindle rate and aneuploidy rate with impaired mitochondrial function in the MII oocytes from 8-week-old mice. Upon CTX treatment at 8-week-old, the oocyte competence and folliculogenesis from the oocyte-specific Clpp knockout mice was further deteriorated with dramatic impairment of mitochondrial distribution and function including elevated ROS level, decreased mitochondrial membrane potential, respiratory chain activity and ATP production. Taken together, the results indicate that that ClpP was required for oocyte competence during maturation and early folliculogenesis, and its deficiency deteriorate cyclophosphamide-induced ovarian damage.